Wewenang Pengawasan Pemerintah Daerah Kabupaten Timor Tengah Utara Terhadap Pengelolaan Badan Usaha Milik Desa - Feka, Gratiana Trifonia; Tuba Helan, Yohanes G; Asnawi, Norani (Artemis Law Journal, 2024)
The main problems of this research are: (1) How is the implementation of supervision of the Regional Government of North Central Timor Regency on the management of Village-Owned Enterprises? (2) Are there any obstacles in the use of supervisory authority of the Regional Government of North Central Timor Regency on the management of Village-Owned Enterprises? This research is an empirical juridical research. Data collection techniques are carried out by: interviews, literature studies, and documentation. The analysis technique used is qualitative descriptive. Results and discussion: (1) The supervisory authority of BUMDes has not been maximized, there is still abuse of authority. (a) Preventive Supervision Authority: In Lemon Village BUMDes the staffing authority has been running well according to their respective authorities, in Leo Sikun BUMDes Saenam Village supervision has not been maximized due to abuse of authority and no follow-up. In the PMD Service, supervision is routine and runs according to its authority, duties and functions. (b) Repressive Supervision Authority: in the PMD Office the follow-up action carried out is by conducting coaching, monitoring and evaluation. In BUMDes Lemon, follow up on existing obstacles by discussing with PEMDES. At BUMDes, Leo Sikun followed up by discussing with PEMDES, the community during MusDes and will be submitted to the PMD Office. However, until now there has been no change. (2) There are constraints in the supervisory authority: (a) Human Resources: in Lemon Village and Saenam Village the level of education is not very good and the need for attention from the PEMDES. (b) Facilities and Infrastructure: in Lemon Village there is no BUMDes office and also lack of supporting facilities in the form of computers. Meanwhile, in Saenam Village, facilities and infrastructure are sufficient, but there is no coordination between administrators and supervisors